IMPROVING THE SOWING QUALITIES OF GRAIN SEEDS (Modern American Journal of Biological and Environmental Sciences, 2026)
Agricultural production imposes certain requirements on the quality of seed material. The higher the varietal purity of the seeds, the more fully their productive properties manifest themselves. Another important role is played by the purity of the seed material – the absence of foreign impurities in it. Germination of seeds is the main indicator of their sowing qualities. These requirements are due to the fact that when sowing seeds with reduced purity and germination, it is necessary to increase the seeding rates. In addition to high sowing qualities and high purity, seeds must also have high yield properties.